Ni–Mo–O nanorod-derived composite catalysts for efficient alkaline water-to-hydrogen conversion via urea electrolysis. Issue 7 (22nd May 2018) - Yu, Zi-You; Lang, Chao-Chao; Gao, Min-Rui; Chen, Yu; Fu, Qi-Qi; Duan, Yu; Yu, Shu-Hong
Abstract : Two Ni–Mo–O compounds show exceptional cathodic/anodic catalytic performance for urea electrolysis, suggesting a promising route to energy-saving H2 production. Abstract : Photo/electrochemical splitting of water to hydrogen (H2 ) fuel is a sustainable way of meeting our energy demands at no environmental cost, but significant challenges remain: for example, the sluggish anodic reaction imposes a considerable overpotential requirement. By contrast, urea electrolysis offers the prospect of energy-saving H2 production together with urea-rich wastewater purification, whereas the lack of inexpensive and efficient urea oxidation reaction (UOR) catalysts places constraints on the development of this technique. Here we report a porous rod-like NiMoO4 with high oxidation states of the metal elements enabling highly efficient UOR electrocatalysis, which can be readily produced through annealing solid NiMoO4 · x H2 O as a starting precursor in Ar. This precursor gives the derived Ni/NiO/MoO x nanocomposite when switching the shielding gas from Ar to H2 /Ar, exhibiting platinum-like activity for the hydrogen evolution reaction (HER) in alkaline electrolytes. Assembling an electrolytic cell using our developed UOR and HER catalysts as the anode and cathode can provide a current density of 10 milliamperes per square centimeter at a cell voltage of mere 1.38 volts, as well as remarkable operational stability, representing the best yet reported noble-metal-free urea electrolyser. Our results demonstrate the potential of nickel–molybdenum-based materials as efficient electrode catalysts for urea electrolysers that promises cost-effective and energy-saving H2 production.